Long-Term Evaluation of Nasal Septoplasty Followed by Inferior Turbinate Cauterization for the Treatment of Nasal Obstruction Using Objective and Subjective Methods - Valsamidis,Konstantinos (2018)
Abstract Introduction Nasal septoplasty is considered the treatment of choice for nasal obstruction due to septal deviation. An ongoing discussion among rhinologists is whether it is reasonable to perform objective measurements of nasal patency pre or postoperatively routinely. Objective The primary aim of this study was to identify the short- and long-term functional benefits for patients undergoing septal surgery, as assessed by acoustic rhinometry (AR). The secondary goal was to evaluate the short- and long-term perception of symptom relief and disease-specific quality of life (QoL) outcomes on the part of the patients. Methods This was a prospective observational study in which AR was utilized for the assessment of nasal patency preoperatively and 1, 6 and 36months after septoplasty. Total 40 patients who underwent septoplasty filled out the Nasal Obstruction Septoplasty Effectiveness (NOSE) questionnaire and the Glasgow Benefit Inventory (GBI) to assess their subjective improvement in nasal obstruction symptoms and the changes in their QoL. Results There were statistically significant improvements in nasal patency, mean postoperative NOSE and GBI scores postoperatively. However, there was no correlation between the mean NOSE and GBI scores and the AR measurements. Furthermore, the GBI scores tended to decrease as the postoperative period increased. Conclusion The present study confirms that septoplasty significantly increases nasal patency and causes a significant subjective improvement in nasal obstruction symptoms. The absence of a statistically significant correlation among the objective measurements, the symptom scores, and the patients’ low GBI scores indicates that factors other than the anatomical findings may also contribute to the patients’ perception of QoL.